Extracorporeal multi-organ support: ECMO, CRRT, and hemoperfusion for acute alcohol intoxication with renal and respiratory failure - Xiting Dang; Shuzhi Lv; Miao Huang; Huini Fu (Renal Failure)
Introduction Acute alcohol intoxication can lead to severe complications, including acute kidney injury (AKI), acute respiratory distress syndrome (ARDS), and systemic inflammatory response syndrome (SIRS). Conventional treatments often fail to stabilize critically ill patients, necessitating advanced extracorporeal life support. This study evaluates the effectiveness of extracorporeal membrane oxygenation (ECMO) combined with continuous renal replacement therapy (CRRT) and hemoperfusion (HP) in managing multi-organ failure after acute alcohol intoxication.Methodology A critically ill patient with alcohol-induced esophageal perforation, ARDS, and AKI was treated with ECMO, CRRT, and HP after conventional therapies proved insufficient. CRRT was used for fluid management and renal support, while HP facilitated cytokine removal to mitigate inflammation. The clinical course was monitored using respiratory parameters, renal function markers, inflammatory cytokine levels, and hemodynamic stability.Results The combination therapy improved oxygenation, stabilized renal function, and reduced systemic inflammation. The patient successfully underwent surgical repair for esophageal perforation and showed full recovery at two-year follow-up.Conclusion Integrating CRRT and HP into ECMO circuits offers a novel and effective approach for managing renal dysfunction in acute alcohol intoxication. This strategy may improve outcomes in critically ill patients requiring extracorporeal support. Further studies are needed to optimize its clinical application.